2013
DOI: 10.1371/journal.pone.0066150
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Gene Expression Analysis of Bordetella pertussis Isolates Associated with a Resurgence in Pertussis: Elucidation of Factors Involved in the Increased Fitness of Epidemic Strains

Abstract: Bordetella pertussis (B. pertussis) is the causative agent of whooping cough, which is a highly contagious disease in the human respiratory tract. Despite vaccination since the 1950s, pertussis remains the most prevalent vaccine-preventable disease in developed countries. A recent resurgence pertussis is associated with the expansion of B. pertussis strains with a novel allele for the pertussis toxin (ptx) promoter ptxP3 in place of resident ptxP1 strains. The recent expansion of ptxP3 strains suggests that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
63
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 44 publications
4
63
1
1
Order By: Relevance
“…Surprisingly, the SNP cluster I strain also outcompeted the SNP cluster II strain in the naïve host environment, suggesting that the SNP cluster I strain has evolved to achieve better fitness regardless of the host environment. Our findings are supported by a previous report by King et al [20] which compared the colonisation difference between Dutch pxtP3 and ptxP1 strains which were equivalent to our SNP cluster I and SNP cluster II strains, respectively. They also found better colonisation of wild-type ptxP3 strains in the lungs and trachea of naïve mice when assessed at day 4 of the infection [20].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Surprisingly, the SNP cluster I strain also outcompeted the SNP cluster II strain in the naïve host environment, suggesting that the SNP cluster I strain has evolved to achieve better fitness regardless of the host environment. Our findings are supported by a previous report by King et al [20] which compared the colonisation difference between Dutch pxtP3 and ptxP1 strains which were equivalent to our SNP cluster I and SNP cluster II strains, respectively. They also found better colonisation of wild-type ptxP3 strains in the lungs and trachea of naïve mice when assessed at day 4 of the infection [20].…”
Section: Discussionsupporting
confidence: 92%
“…Our findings are supported by a previous report by King et al [20] which compared the colonisation difference between Dutch pxtP3 and ptxP1 strains which were equivalent to our SNP cluster I and SNP cluster II strains, respectively. They also found better colonisation of wild-type ptxP3 strains in the lungs and trachea of naïve mice when assessed at day 4 of the infection [20]. Furthermore, they found that the advantage of ptxP3 strains also depended on their genetic background [20].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Although the ptxP3 allele is thought to increase pertussis toxin expression (40,41), a recent comparison of isogenic mutants found that the ptxP3 allele and the genetic background, which includes genomic structure, independently enhance colonization in mice (42). Similarly, although alleles of fimH contain polymorphisms in the predicted surface epitope region, differences in immune recognition remain untested (43).…”
Section: Discussionmentioning
confidence: 99%
“…With the observed increase of pertussis in various vaccinating countries in recent years, antigenic mutations were reported in circulating B. pertussis strains [61][62][63][64]. Global transmission of new strains is very rapid and the worldwide population of B. pertussis is evolving in response to vaccine introduction [65].…”
Section: Issues With Kendrick Testmentioning
confidence: 99%